Editor's Note (TEL Tempo, Espaço e Linguagem, 2020)
Bearing in mind the emergence of gender studies today and the contemporary socio-political demands that are increasingly latent due to complex approaches on the theme, we have launched here the dossier “Gender, discursivities and transversalities” which aimed to combine several researches that use the concept as a category of analysis and thinking from and about it. We consider that addressing gender studies contributes to our understanding of ethical and political organizations in different social and historical areas, unraveling cultural relations and, essentially, the plots and flows of power relations within certain societies, time and language.